2010
DOI: 10.1111/j.1537-2995.2009.02573.x
|View full text |Cite
|
Sign up to set email alerts
|

DIIIa and DIII Type 5 are encoded by the same allele and are associated with altered RHCE*ce alleles: clinical implications

Abstract: BACKGROUND-The partial D phenotype DIIIa was originally reported to be associated with 455A>C in Exon 3, 602C>G in Exon 4, and 667T>G in Exon 5. Other alleles with these changes were subsequently identified and designated DIII Types 5, 6, and 7, as they had additional alterations. The observation that DNA samples associated with the DIIIa phenotype had more changes than those originally reported motivated us to reanalyze the DIIIa probands (BP and DJ) from the original study. We also studied additional DIIIa s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 22 publications
1
56
0
Order By: Relevance
“…Three of four patients with the 667C>G mutation were from the HbSS group, providing an estimate of the incidence of a partial D genotype DIIIa, of 2.2% of these patients. These findings corroborate the observation that a high frequency of this mutation is common in people of African origin and uncommon among individuals with a Caucasian genetic heritage [8].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Three of four patients with the 667C>G mutation were from the HbSS group, providing an estimate of the incidence of a partial D genotype DIIIa, of 2.2% of these patients. These findings corroborate the observation that a high frequency of this mutation is common in people of African origin and uncommon among individuals with a Caucasian genetic heritage [8].…”
Section: Discussionsupporting
confidence: 81%
“…All samples containing the HincII restriction enzyme site had the 667C>G (exon 5) mutation in the RHD gene and were subjected to a second PCR reaction to search for the 455A>C (exon 3) and the 1025T>C (exon 7) mutations. The DNA fragment amplified by PCR was digested with the BanI restriction enzyme, to identify the 455A> C mutation specific for the DIIIa allele, and by the HphI restriction enzyme, to identify the 1025T>C mutation specific for the DAR allele [8,9].…”
Section: Molecular Biology Analysismentioning
confidence: 99%
“…Corroborating Noizay study, Chou and Westhoff have shown that variants of the RhD gene are of great relevance in transfusion medicine for sickle cell patients, they have shown that 22% of patients with sickle cell disease african Americans have this hybrid gene, resulting in changes in some epitopes of the RhD protein, leading these patients to be phenotyped as normal RhD positive and, though on receiving RhD positive red cells, develop Anti-D Antibodies. Agreeing with study Noizat, Westhoff and colleagues studied serologically and molecularly 39 African-American patients, of which the study serologic 18 (46.15%) had anti-D [26]. Corroborating work Westhoff et al [26] and Castilho et al [27] also demonstrated that in african-Brazilians there is a high frequency of variant DIIIa and DAR, too suggesting a high risk individuals such alloimmunization, leading to a reduction of the lifetime of the erythrocytes in circulation [27].…”
Section: Discussionmentioning
confidence: 99%
“…Corroborating work Westhoff et al [26] and Castilho et al [27] also demonstrated that in african-Brazilians there is a high frequency of variant DIIIa and DAR, too suggesting a high risk individuals such alloimmunization, leading to a reduction of the lifetime of the erythrocytes in circulation [27]. Unlike Westhoff et al [26]and Castilho et al [27], our results show a higher frequency of DF5 variant in patients with sickle cell disease, This also contrasts with the literature, since DF5 variant is more frequent in Caucasians [28]. Our study also diverges with Müller et al [28], where it was demonstrated that among the variants of the weak D type, the most frequent are respectively variants weak D types 1,2,3,4 and 5, being less frequent variant DF5 of these cited and still, In the same study it was not reported any alloimmunization for anti-D in patients characterized with some of these variants [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation